Entrance, Marshall Sons and Co. building - Ghosh, Ayan (2023)
Entrance to Marshall Sons and Co. building, at the intersection of Shoorji Vallabhdas Road and Shahid Bhagat Singh Marg. The entrance has a round pediment with two life-size female figures seated in the spandrel. The year of its construction, 1906, is inscribed above the keystone.